الوسائل التعليمية ودورها في تعليم اللغة العربية للناطقين بغيرها - الغالية, العالية (جامعة الوادي - University of Eloued, 2019)
أضحى استخدام الوسائل التّعليميّة على اختلافها سمعيّة أو بصريّة أو سمعيّة بصريّة في السنوات الأخيرة أمرا ضروريا في عملية التعليم عامّة وتعليم اللّغات بخاصة، وإنّنا لفي عصر تكنولوجيّات والتطوّرات العلميّة في شتى المجالات المعرفية والفكرية نسعى إلى مواكبة هذه التطوّرات الحاصلة من أجل الرقيّ بمجال تعليم اللّغات عامة واللغة العربية بوجه خاص، وإيجاد طرائق وتقنيّات تكون عونا ومساعدا لمتعلمي اللغة العربية للناطقين بغيرها وتيسير أمرها، ومن ثمّة تجعل مدّة الدّراسة أقصر من الوقت الماضي، فالوسيلة الجيّدة تنير اهتمام المتعلّم وتشوقه إلى متابعة الدّرس والسيّر قدما إلى الأمام. In recent years, the use of educational aids in various fields of audio, visual or audiovisual has become necessary in the process of education in general and language education in particular. In the age of scientific technologies and developments in various fields of knowledge and intellect, we seek to keep abreast of these developments in order to improve the field of general language education and language Especially in Arabic, and to find methods and techniques that will help and assist the learners of the Arabic language for non-Arabic speakers and facilitate them, and thus make the duration of study shorter than the last time, a good means enlighten the attention of the learner and eager to follow And move forward. Therefore, the study explained the concept of educational means, their types and their role in teaching Arabic to non-Arabic speakers.
Teaching Aids And Their Role In Teaching Arabic To Non-native Speakers
مقال
Keywords: الوسائل التعليمية؛ دورها؛ تعليم اللغة العربية؛ الناطقين بغيرها; educational aids; their role; teaching Arabic; speakers